The impact of age and preoperative health-related quality of life on patient-reported improvements after total hip arthroplasty - Aalund PK (Dove Medical Press, 2017)
Peter K Aalund, Eva N Glassou, Torben B Hansen University Clinic for Hand, Hip and Knee Surgery, Regional Hospital West Jutland, Aarhus University, Holstebro, Denmark Background: Total hip arthroplasty (THA) is a common surgical procedure and approximately 9,500 of these surgeries are performed annually in Denmark. The operation is considered effective and successful with respect to complications, mortality, and implant survival. However, using patient-reported outcome measures, up to 10% of patients are not satisfied with the outcome of their operation. To address this, it is important to find out why some patients experience impaired outcomes after THA. The purpose of this study was to investigate the impact of age and preoperative health-related quality of life (HRQoL) on improvements in HRQoL after THA.Methods: A cohort study was conducted with follow-up at 3 and 12 months. Patients were included from September 2008 to December 2013. We analyzed 1,283 THA cases. HRQoL was measured using the EuroQol-5 Domain. Analyses were carried out with multiple linear regression and adjusted for relevant variables available in the data set.Results: A significant positive association was found between age and HRQoL outcomes for patients who underwent THA at both 3 (β [regression coefficient] 0.0026, confidence interval [CI] 0.0013; 0.0039, p<0.001) and 12 (β 0.0020 CI 0.0008; 0.0032, p=0.001) months of follow-up. A clinically relevant change was achieved with an increase in age of 12–15 years. A significant negative association was found between preoperative HRQoL and HRQoL outcomes at both 3 (β−0.841 CI−0.886; −0.795, p<0.001) and 12 (β−0.804 CI−0.844; −0.764, p<0.001) months of follow-up.Conclusion: Contrary to our expectations, older patients had more improvements in HRQoL outcomes after THA. A high preoperative HRQoL seems to inhibit improvements in HRQoLs after THA. Keywords: total hip arthroplasty, THA, health-related quality of life, HRQoL, EuroQol-5D, patient-reported outcome